Potential Vegetation for Soil and Water Conservation: Case Study in Samin Watershed, Central Java - Maridi, M; Agustina, Putri; Saputra, Alanindra (Universitas Muhammadiyah Surakarta, 2015)
Samin is one of watersheds located in the districts of Karanganyar and Sukoharjo, Central Java, Indonesia. Samin is a part of Bengawan Solo watershed that is classified into one of 282 Indonesian watersheds which are in critical condition. Research about vegetation analysis of Samin watershed as conservation efforts have been done before and resulted in structure of lower crop community (LCC) and tree vegetation. The purpose of this study was to analyze potential plants, both LCC and trees, in Samin watershed that could be developed as a vegetative water and soil conservation. The list of plants that were potentially developed as a vegetative conservation obtained from the research before about analysis structure and composition of vegetation in Samin watershed and literature review. The result of this research showed that there were several plants with the highest Important Value Index (IVI) and that can be developed for vegetative soil and water conservation. In tree vegetation, there are Tectona grandis, Delonix regia, Switenia mahagoni, Cassia siamea, and Samanea saman. These tree plants have a big canopy that can retain rain water through several mechanismssuch as interception, reducing direct flow, and producing litter layer. In LCC vegetation, there were Mimosa pudica, Ageratum conyzoides, Tridax procumbens, Oplismenus burmanii, Chloris barbata, and Axonopus compressus. Grass vegetation could withstand runoff and increase infiltration.